Naissance d’une critique ? La présence de l’occitan dans la presse béarnaise de la fin du XVIIIe siècle - Jean-François Courouau (Lengas)
The presence of the Occitan language in the press doesn't date back to the 19th century as generally admitted. Already in the last decades of the 18th century, some experiences were made, especially in Béarn. A lawyer established in Pau, Nicolas Suberbie-Cazalet (1743-1817), supervises the publication of a Circulaire des Pyrénées with 49 issues published in 1778-1779. The undertaking ends in failure but some years later a new publication emerges in the form of a Tableau annuel du Béarn (1784-1787). In each of these publications, the Occitan language (Béarnais) is present through poems but sometimes too through critical reviews or literary judgements. The presence of Occitan in the press of Béarn demonstrates a legitimacy in spite of a thin market and the insufficient dynamism of the literary production.